SISTEM INFORMASI PENCATATAN DAN PERHITUNGAN BIAYA PENGGUNAAN AIR BERSIH BERBASIS ANDROID - Khadhik Al amin; Jarot Dian Susatyono (STEKOM PRESS, 2018)
Abstract Recording and processing of data previously implemented is still manual. ie the field officer records it into a notebook containing data of the names of customers, then a book containing data on the usage figures on the water meter is submitted to the treasurer to calculate the total cost to be paid, but in the calculation process is still manual, the officer must read the data in the book then calculated using a calculator which is then the result of the calculation is written into a water bill as proof of payment. Information systems of water use make it simplify and speed up the process of calculation and recording. It can be done by inputting a number on the water meter which is the amount of the amount of water usage in the form or an order to enter numbers, the input data of these numbers can then be processed automatically calculation of the cost of water use based on figures from water meters. for storing the data will be sent to the server and the database. Keywords: SIA, PAD, Ratio of Digest Method The recording and processing of data previously applied is still manual. ie the field officer records it into a notebook containing data of the names of customers, then a book containing data on the usage figures on the water meter is submitted to the treasurer to calculate the total cost to be paid, but in the calculation process is still manual, the officer must read the data in the book is then calculated using a calculator which is then written into the water bill as proof of payment. Water Usage Information System costs simplify and speed up the calculation and recording process, then make it by inputting a number on the water meter which is the amount of the amount of water usage in the form or an order to enter numbers, the input data numbers can then be processed automatically calculation of the cost of water use based on figures from the water meter. for storing the data will be sent to the server and stored into the database.